Development and characterization of a prototypic pan-amyloid clearing agent – a novel murine peptide-immunoglobulin fusion - Foster, James S.; Balachandran, Manasi; Hancock, Trevor J.; Martin, Emily B.; Macy, Sallie; Wooliver, Craig; Richey, Tina; Stuckey, Alan; Williams, Angela D.; Jackson, Joseph W.; Kennel, Stephen J.; Wall, Jonathan S. (Frontiers in Immunology, 2023)
Abstract Introduction: Systemic amyloidosis is a progressive disorder characterized by the extracellular deposition of amyloid fibrils and accessory proteins in visceral organs and tissues. Amyloid accumulation causes organ dysfunction and is not generally cleared by the immune system. Current treatment focuses on reducing amyloid precursor protein synthesis and slowing amyloid deposition. However, curative interventions will likely also require removal of preexisting amyloid deposits to restore organ function. Here we describe a prototypic pan-amyloid binding peptide-antibody fusion molecule (mIgp5) that enhances macrophage uptake of amyloid. Methods: The murine IgG1-IgG2a hybrid immunoglobulin with a pan amyloid-reactive peptide, p5, fused genetically to the N-terminal of the immunoglobulin light chain was synthesized in HEK293T/17 cells. The binding of the p5 peptide moiety was assayed using synthetic amyloid-like fibrils, human amyloid extracts and amyloid-laden tissues as substrates. Binding of radioiodinated mIgp5 with amyloid deposits in vivo was evaluated in a murine model of AA amyloidosis using small animal imaging and microautoradiography. The bioactivity of mIgp5 was assessed in complement fixation and in vitro phagocytosis assays in the presence of patient-derived amyloid extracts and synthetic amyloid fibrils as substrates and in the presence or absence of human serum. Results: Murine Igp5 exhibited highly potent binding to AL and ATTR amyloid extracts and diverse types of amyloid in formalin-fixed tissue sections. In the murine model of systemic AA amyloidosis, 125I-mIgp5 bound rapidly and specifically to amyloid deposits in all organs, including the heart, with no evidence of non-specific uptake in healthy tissues. The bioactivity of the immunoglobulin Fc domain was uncompromised in the context of mIgp5 and served as an effective opsonin. Macrophage-mediated uptake of amyloid extract and purified amyloid fibrils was enhanced by the addition of mIgp5. This effect was exaggerated in the presence of human serum coincident with deposition of complement C5b9. Conclusion: Immunostimulatory, amyloid-clearing therapeutics can be developed by incorporating pan-amyloid-reactive peptides, such as p5, as a targeting moiety. The immunologic functionality of the IgG remains intact in the context of the fusion protein. These data highlight the potential use of peptide-antibody fusions as therapeutics for all types of systemic amyloidosis.